Arguing a business tort against auditors / Loganathan Krishnan - Loganathan, Krishnan (2010)
The term ‘auditor’ originates from the expression auditor, which in Latin, it means ‘to listen’. Nonetheless, when scrutinising the duties and obligations of auditors, it reveals that they do not merely listen. They also examine and report to the company, on its accounts. Moreover, the scope of these duties and obligations has amplified over recent years. This is due to the changes in the corporate landscape which encompasses the business world. Fundamentally, judgments have been pronounced by the courts across jurisdictions with regards to auditors’ liability in tort. This can be seen in the historic English decision of Re Kingston Cotton Mill Co (No 2) [1896] 2 Ch 673, whereby Lopes LJ stated that “...auditors are watchdogs but not bloodhound…” Additionally, it can be observed in the ingenious statement of Cardozo CJ in the American decision of Ultramares Corporation v Touche (1931) 174 NE 441 whereby he stated that to hold auditors liable results to a case of “…liability of an indeterminate amount for an indeterminate time to an indeterminate class…” In the midst of these legal pronouncements, it is pertinent to determine the liability of auditors under tort in Malaysia, which was distilled in 1967. Essentially, the current legal framework governing auditors must be reassessed in the wake of the scandals involving auditors both in the domestic and international forefront. The study then explores the appropriate litmus test in determining a claim for tort against auditors. A comparative study is also carried out as regards to the legal position in United Kingdom, Australia and New Zealand to determine the approach taken by the courts. Fundamentally, principles of business law have to play its role effectively to ensure that the interests of all parties who have a stake in the matter are well- balanced with the liability of auditors.